Determination of In Vitro Antimicrobial Susceptibility for Lefamulin (Pleuromutilin) for Ureaplasma Spp. and Mycoplasma hominis - Oliver Spiller-Boulter (MDPI AG, 2021)
Lefamulin is the first of the pleuromutilin class of antimicrobials to be available for therapeutic use in humans. Minimum inhibitory concentrations of lefamulin were determined by microbroth dilution for 90 characterised clinical isolates (25 Ureaplasma parvum, 25 Ureaplasma urealyticum, and 40 Mycoplasma hominis). All Mycoplasma hominis isolates possessed lefamulin MICs of ≤0.25 mg/L after 48 h (MIC50/90 of 0.06/0.12 mg/L), despite an inherent resistance to macrolides; while Ureaplasma isolates had MICs of ≤2 mg/L after 24 h (MIC50/90 of 0.25/1 mg/L), despite inherent resistance to clindamycin. Two U. urealyticum isolates with additional A2058G mutations of 23S rRNA, and one U. parvum isolate with a R66Q67 deletion (all of which had a combined resistance to macrolides and clindamycin) only showed a 2-fold increase in lefamulin MIC (1–2 mg/L) relative to macrolide-susceptible strains. Lefamulin could be an effective alternative antimicrobial for treating Ureaplasma spp. and Mycoplasma hominis infections irrespective of intrinsic or acquired resistance to macrolides, lincosamides, and ketolides. Based on this potent in vitro activity and the known good, rapid, and homogenous tissue penetration of female and male urogenital tissues and glands, further exploration of clinical efficacy of lefamulin for the treatment of Mycoplasma and Ureaplasma urogenital infections is warranted.